Effect of aerobic exercise on body composition of overweight female; inspiring university students to practice and receive more advantageous way of life - Razia Nawaz; Wasim Khan; Ratko Pavlović; Tasleem Arif; Sardar Nasir Sohail (University of Banja Luka, Faculty of physical education and sport, 2020)
The purpose of this study aimed to look at assessing the effects of aerobic exercise on body composition of overweight female aging 22-27 years.A sample of n=30 (thirty) overweight female aging 22-27 years in District Tonsa (Punjab), Pakistan were included as subject. A four (04) week exercise protocol was prepared and used among females of the experimental group. The experimental group was subjected to measure the anthropometric as well as 3- site skin fold measurements. The data regarding pre and post-test of both groups-control and experimental were carefully recorded and entered into the computer for analyses. For this purpose, both descriptive (mean and standard deviation) and inferential statistics (Independent Samples t-Test and Paired Samples t-Test) were used for analyzing the data. The analyzed data established that the mean score of (EG) in pre and post-test were found as 28.66 and 23.5. The t-value of the table is 5.022 and P-value is 0.001 which is lower than the significant level (P<0.05). Therefore, it is concluded that the difference between Pre and Post-test of Control Group has shown the significant effects of aerobic exercises on body fat percentage of overweight females. According to the analyzed data the mean value of Post-tests regarding body fat percentage of Control Group were 28.89 and Experimental Group was 23.5. The P-value 0.002 and t-value -987 in the table depict the significant statistical difference between the two means of Control and Experimental Group in Body Mass Index (P<0.05).The results of the study indicated that the four weeks' aerobic exercise protocol has a significant effect on overweight females in the perspective of decreasing their body fat percentage. Based on the findings, the researcher recommended that more and more involved in physical activity and exercise among female folk may be ensured.